ITS2-rDNA fragments of Leishmania species isolated from the great gerbil in Iran, 2021 - Shirazian , Maryam; Taghipour, Niloofar; Akhavan, Amir Ahmad; Seyyed Tabaei, Seyyed Javad; Mosaffa, Nariman; Abaei, Mohammad Reza; Akrami, Ali Reza; Moin vaziri, Vahideh (Novelty in Biomedicine, 2023)
Background: The great gerbil (Rhombomys opimus), is widely distributed in Asia and is a natural reservoir for zoonotic cutaneous leishmaniasis in many endemic areas, as well as Iran. Materials and Methods: In this study, infection to Leishmania species was investigated by two methods, parasitological and molecular survey, in the small number of R. opimus collected from Jovain, a Zoonotic Cutaneous Leishmaniasis (ZCL) focus located in North East of Iran. Results: Parasitological observation showed infection in only one of five rodents. But, ITS2-Nested-PCR revealed Leishmania infection in three out of 5 gerbils, including the parasitological positive one. Based on the PCR amplified size, two cases of infections were Leishmania major and one Leishmania turanica, their sequences are accessible in GenBank. The results of sequence analysis were consistent with the results obtained based on the size of the PCR. Conclusion: These findings re-confirm the important role of R. opimus in the natural circulation of Leishmania spp and indicate the need to be concerned about the disease in the study area.